Prosecuting for the environment ipagtanggol ang kalikasan! conference proceedings, February 21-24, 2000, Legend Hotel, Puerto Princesa City, Palawan - Gutierrez, Ronaldo R.; Manalo, Joseph S. (Tanggol Kalikasan, Inc., 2000)
Part I: The Philippine environment : its importance and state -- Part II: Philippine environmental laws and policies -- Part III: Defining the nexus : prosecution and conservation -- Part IV: Challenges in the prosecution of environmental cases from an NGO perspective.